Absence of MerTK disrupts spermatogenesis in an age-dependent manner. (15th January 2023) - Shi, Jie; Gao, Sheng; Chen, Zhengru; Chen, Zifeng; Yun, Damin; Wu, Xiaolong; Sun, Fei
Abstract: Spermatogenesis is a highly specialized cell differentiation process regulated by the testicular microenvironment. During the process of spermatogenesis, phagocytosis performs an essential role in male germ cell development, and its dysfunction in the testis can cause reproduction defects. MerTK, as a critical protein of phagocytosis, facilitates the removal of apoptotic substrates from the retina and ovaries through cooperation with several phagocytosis receptors. However, its role in mammalian spermatogenesis remains undefined. Here, we found that 30-week-old MerTK −/− male mice developed oligoasthenospermia due to abnormal spermatogenesis. These mice showed damaged seminiferous tubule structure, as well as altered spermatogonia proliferation and differentiation. We also found that Sertoli cells from MerTK −/− mice had decreased phagocytic activity on apoptotic germ cells in vitro . Moreover, a transcriptomic analysis demonstrated that the pivotal genes involved in spermatid differentiation and development changed expression. These results indicate that MerTK is crucial for spermatogenesis, as it regulates the crosstalk between germ cells and Sertoli cells. This provides us insight into the molecular mechanism of MerTK on spermatogenesis and its implications for the diagnosis and treatment of human male infertility. Graphical abstract: Image 1 Highlights: MerTK-deficient mice showed severe oligoasthenospermia in an age-dependent way. Loss of MerTK disrupts spermatogonia and spermatids development. MerTK enables Sertoli cells to recognize and phagocytosis on apoptotic germ cells. MerTK regulates expression of genes involved in the process of spermatogenesis.